1994
DOI: 10.2166/wst.1994.0659
|View full text |Cite
|
Sign up to set email alerts
|

Estimations for Percentage of Impervious Area by the Use of Satellite Remote Sensing Imagery

Abstract: This study aims to evaluate the applicability of satellite imagery in estimating the percentage of impervious area in urbanized areas. Two methods of estimation are proposed and applied to a small urbanized watershed in Japan. The area is considered under two different cases of subdivision; i.e., 14 zones and 17 zones. The satellite imageries of LANDSAT-MSS (Multi-Spectral Scanner) in 1984, MOS-MESSR(Multi-spectral Electronic Self-Scanning Radiometer) in 1988 and SPOT-HRV(High Resolution Visible) in 1988 are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Kite et al (1992) apply semi-distributed watershed modelling, which requires prior knowledge about land cover classes (bare ground, forests and grass). Deguchi and Sugio (1994) evaluate the applicability of satellite imagery for estimating the percentage of impervious area in a scene with the goal of using it for runoff simulation in urban areas. In their work, land cover classification is achieved by clustering algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Kite et al (1992) apply semi-distributed watershed modelling, which requires prior knowledge about land cover classes (bare ground, forests and grass). Deguchi and Sugio (1994) evaluate the applicability of satellite imagery for estimating the percentage of impervious area in a scene with the goal of using it for runoff simulation in urban areas. In their work, land cover classification is achieved by clustering algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand aerial photographs have previously been used as ancillary data to validate the accuracy of land cover maps generated from remotely sensed satellite imagery (Mas, 2003;Rembold et al, 2000;Wentz et al, 2006;Deguchi and Sugio, 1994). Deguchi and Sugio (1994).…”
Section: Introductionmentioning
confidence: 99%
“…They further noted that differences in levels of accuracy using the three methods arise from positional errors, incorrect ground observations, or discrepancies between the sizes of sampling unit in the ground versus classes generated. Hara et al, (2005) used aerial photographs to determine transformation on the urban fringe of Bangkok, Thailand, while Deguchi and Sugio (1994) cited by Wentz et al, (2006) compared aerial photography and a variety of satellite datasets for impervious areas and the density of urbanized area of Wake County in the state of North Carolina, USA. The two studies concluded that both aerial photography and satellite data returned results of similar accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Remote sensing has long been used for land use/land cover (LULC) classification, and it allows up-to-date, spatially explicit estimates of urban surface imperviousness over large areas. [9][10][11] Ridd proposed the classic vegetation-impervious surface-soil model to parameterize biophysical composition of urban environments. 12 Carlson and Arthur retrieved the fraction impervious surface of Chester Country based on the inverse relationship between impervious surfaces and vegetation.…”
Section: Introductionmentioning
confidence: 99%